The Impact of Project-Based Learning on Students’ Writing Skills in EFL Contexts - Vivit Rosmayanti; Muthi'ah (JURNAL PENDIDIKAN BAHASA DAN BUDAYA, 2025)
This research addresses the impact of Project-Based Learning (PjBL) on learners' writing skills, motivation, and engagement within the English as a Foreign Language (EFL) setting. While it is known that PBL, involving the completion of real-life projects, helps improve writing skills, its motivational impacts, especially concerning the writing capability of EFL students, remain understudied. The study aimed to determine the extent of PBL’s effect on students’ writing skills with a specific focus on grammar, coherence, creativity, argumentation, and motivation toward writing activities. The research used qualitative methods through conducting interviews, document analysis of student projects, and thematic analysis to identify pivotal themes from the gathered data. The findings indicate that these students not only became more creative and skilled in writing, but also became more motivated and engaged as a result of task relevancy, technology, and self-reflection and feedback opportunities. The study found that PjBL has a significant impact on students' writing skills and motivation, while providing tangible phenomena and enriching constructive perspectives on writing lessons within EFL contexts. It strongly suggests that clearer direction on time allocation, genre adjustment, PBL collaborative learning, and ongoing feedback should be employed in future studies.